Spritual Leadership Dalam Pendidikan Islam - Yona Yohara Safutri; Diana Riski Sapitri Siregar (Jurnal Administrasi Pendidikan Islam, 2022)
The desired leadership in Islamic education today is a reliable, trusted and able to actualize constructive changes. Leadership capable of transforming the character of the organization, providing changes and strategies, as well as being able to increase the potential of the individuals they lead, effectively managing resources and having the desire to be actively involved in the process of innovation and growth, and have the spirit to achieve and pursue success without dominated by materialism alone. The purpose of this study is to describe spiritual leadership in Islamic education. The results of this study explain that spiritual leadership not only makes the people they lead able to move according to their initial goals, but also provides a fresh vision, a shower for a solid and honest group conscience, and a feeling of belonging to one another. Leadership brings the worldly dimension to the spiritual dimension (divinity). Leaders of Islamic education should emulate spiritual leadership where leaders and their members do a job from the conscience, show the best, have good communication, and are responsible for the mandate carried out. Prophet Muhammad SAW is an educational leader who is an example of spiritual leadership for Islamic education, so that today's leaders are able to create superior and quality Islamic educational institutions.